2015
DOI: 10.5935/0103-507x.20150056
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia after cardiac arrest: outcome predictors

Abstract: Objective The determination of coma patient prognosis after cardiac arrest has clinical, ethical and social implications. Neurological examination, imaging and biochemical markers are helpful tools accepted as reliable in predicting recovery. With the advent of therapeutic hypothermia, these data need to be reconfirmed. In this study, we attempted to determine the validity of different markers, which can be used in the detection of patients with poor prognosis under hypothermia.Methods Data from adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 71 publications
3
43
1
11
Order By: Relevance
“…Lee et al [15] also reported lower initial GCS scores along with nonshockable rhythm, longer time in cardiac arrest and a higher Sequential Organ Failure Assessment (SOFA) score were independent risk factors for mortality, while no association was found between other time variables (pre-induction and induction) and odds for survival. In contrast to previous results, Leão et al [27] showed a correlation between higher mortality at 6 months after cardiac arrest and shorter time to TT.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Lee et al [15] also reported lower initial GCS scores along with nonshockable rhythm, longer time in cardiac arrest and a higher Sequential Organ Failure Assessment (SOFA) score were independent risk factors for mortality, while no association was found between other time variables (pre-induction and induction) and odds for survival. In contrast to previous results, Leão et al [27] showed a correlation between higher mortality at 6 months after cardiac arrest and shorter time to TT.…”
Section: Discussioncontrasting
confidence: 85%
“…A study evaluating heat generation in patients treated with MTH after cardiac arrest revealed an association between greater heat production and better baseline health status, reduced ischemic injury and improved neurologic outcome [26]. A study published by Leão et al [27] showed that, apart from shorter induction time, patients with unfavorable neurologic outcome had a higher incidence of hypoxic-ischemic brain injury on magnetic resonance imagining and a higher concentration of neuron specific enolase. The present results are consistent with these studies [14,15,19,26,27] and might indirectly support the hypothesis that shorter induction time in patients with unfavorable neurological outcome is related to more severe brain injury, since the initial neurologic condition reflected by GCS on admission was a strong outcome predictor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyin MRG'de hipoksik etkilenme bulguları görülen hastalarda prognoz, etkilenme olmayanlara göre 19 kat daha kötüdür (29). Hipoksinin yeri ve prognozla ilgili veriler çelişkilidir.…”
Section: Gereç Ve Yöntemunclassified
“…115 Other studies have shown that the faster the target temperature is reached, the higher the mortality and the worse the neurologic outcome. 116, 117 It is hypothesized that patients with more severe or irreversible neurologic damage are less reactive to low temperatures, so there is less shivering 117 and less requirement for NMB. 118 The relationship between shivering and outcome has yet to be fully elucidated.…”
Section: Respiratory Supportmentioning
confidence: 99%